API IN OPEN BANKING - Abduvahobov Shohruh Xolmo'min o'g'li (Scholar Express Journals, 2023)
In the modern era of digital transformation, open banking systems have emerged as a catalyst for financial innovation and improving customer experience. At the heart of this revolution lies the API (applied programming interfaces), which provide a secure and standardized exchange of financial information between different stakeholders. This article examines the critical role of APIs in open banking systems, highlighting their importance, underlying methods, outcomes, and implications for the financial sector
Keywords: Open bank; API; financial data exchange